Building mobile applications with Java - Marinacci, Joshua (Sebastopol, CA : O'Reilly Media, 2012)
"This project-driven book shows you how to build portable apps with two ... open source frameworks, Google Web Toolkit (GWT) and PhoneGap. With these tools, you'll learn how to write Java code that compiles into cross-platform JavaScript and HTML, and discover how to take advantage of features in several popular devices, such as the camera, accelerometer, and GPS ... [and] package your apps for iOS, webOS, and Android with PhoneGap"--P. [4] of cover.
Greetings, mobile app developers -- Getting started with GWT -- Getting started with PhoneGap -- Customizing your app for mobile -- Building a pure mobile app with GWT Mobile UI -- Advanced mobile optimizations -- Box2D and Canvas -- Next steps.
"Using the Google Web Toolkit and PhoneGap"--P. [1] of cover.
Keywords: Google Web toolkit; Java (Computer program language); Mobile computing -- Programming; Cross-platform software development; Application software -- Development